Nitrous oxide cycling in the Eastern Tropical South Pacific as inferred from isotopic and isotopomeric data. (October 2018) - Casciotti, K.L.; Forbes, M.; Vedamati, J.; Peters, B.D.; Martin, T.S.; Mordy, C.W.
Abstract: The ocean accounts for up to 25% of global emissions of nitrous oxide (N2 O), a potent greenhouse gas. Much of this N2 O flux occurs in upwelling regions near the ocean's oxygen deficient zones (ODZs), areas known for intense N2 O cycling. The Eastern Tropical South Pacific (ETSP) ODZ is one such area, and large uncertainties surround the balance of processes regulating N2 O production and emission in this region. Here we examined the distributions of dissolved N2 O concentration and stable isotopic composition, in concert with nitrate (NO3 - ) and nitrite (NO2 - ) isotopic ratios, to understand the mechanisms that drive N2 O production, consumption, and emission from the ETSP ODZ. Keeling plot analysis identified N2 O production from both nitrification and denitrification (or nitrifier-denitrification) in the near-surface and in the oxycline, where the largest accumulations of N2 O were found. In the N2 O concentration maximum that occurs below the ODZ, a higher 15 N site preference (SP) indicated nitrification was more prominent. Within the ODZ, significant enrichments were apparent in δ 15 N bulk (14–22‰), δ 18 ON2O (68–100‰) and SP (39–60‰), implying active N2 O consumption. Further scrutiny of N2 O isotope data in the ODZ highlights a deviation from the relative increases in δ 18 ON2O and SP expected for bacterial denitrification. At high levels of N2 O consumption, SP increased more than expected for the increase in δ 18 ON2O . This appeared to be due, at least in part, to a decrease in δ 15 N β driven by N2 O production in the ODZ, rather than further increases in δ 15 N α . Isotopic analysis of co-occurring NO3 - and NO2 - suggests that NO3 - may be the dominant source of N2 O in the offshore ETSP ODZ.